Self-Injury During COVID-19: Views From University Students With Lived Experience. Issue 11 (4th November 2022) - Lewis, Stephen P.; Kenny, Therese E.; Pritchard, Tyler R.; Labonte, Lindsay; Heath, Nancy L.; Whitley, Rob
Abstract: Concerns have been raised about the impact of the COVID-19 pandemic on individuals with lived experience of nonsuicidal self-injury (NSSI). Yet, few efforts have explored this. Accordingly, using a mixed-methods approach, we sought to examine whether emerging adults who have self-injured experienced changes in NSSI urges and behavior during the pandemic and what may have accounted for these changes. To do so, university students with lived experience of NSSI completed online questions asking about NSSI and self-reported changes in urges and behavior since the onset of COVID-19. They then answered open-ended questions asking what contributed to these changes and how they have coped during this timeframe. Approximately 80% of participants reported no change or a decrease in NSSI urges and behavior. Participants discussed removal from stressors ( e.g., social stress) that previously evoked NSSI, as well as having time for self-care and to develop resilience as accounting for this. Nevertheless, some participants reported challenges amid the pandemic ( i.e., exacerbated stress, isolation); approximately one fifth of participants reported increases in NSSI urges and behavior. Our findings add to recent evidence that many individuals with prior mental health difficulties, including NSSI, can demonstrate resilience in the face of collective adversity. Research and clinician implications are discussed.